1985
DOI: 10.1177/001698628502900306
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Aptitude and Achievement Status on the Self-System

Abstract: This investigation examined the independent and joint effects of aptitude (gifted vs. normal) and achievement (underachiever vs. achiever) on assessments of the selfsystem in upper elementary-aged children. The gifted group was significantly higher than the average group on selfevaluations of competence, feelings of mastery, and preference for independent decision making. The average group reported a lower level of understanding than the gifted group about the reasons for success and failure outcomes and more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(16 citation statements)
references
References 16 publications
3
13
0
Order By: Relevance
“…Across grade levels and gender groups, gifted students were reported to be less test anxious relative to their non-gifted counterparts. These data are consistent with research by Milgram and Milgram (1976) supporting the more general notion that intellectually gifted students have a lower mean level of social evaluative anxiety than their regular counterparts, whether measured by self-report (Davis & Connell, 1985;Milgram & Milgram, 1976) or physiological indices (Wooding & Bingham, 1988). Furthermore, the "Big-Fish-Little-Pond" effect (for overviews see Marsh, 2005) was vindicated for test anxiety by Zeidner & Schleyer (1999b), who reported that gifted students enrolled in a pullout program showed lower mean levels of test anxiety compared to gifted students in homogenous gifted classes.…”
Section: Anxiety: Trait State and Evaluativesupporting
confidence: 90%
See 1 more Smart Citation
“…Across grade levels and gender groups, gifted students were reported to be less test anxious relative to their non-gifted counterparts. These data are consistent with research by Milgram and Milgram (1976) supporting the more general notion that intellectually gifted students have a lower mean level of social evaluative anxiety than their regular counterparts, whether measured by self-report (Davis & Connell, 1985;Milgram & Milgram, 1976) or physiological indices (Wooding & Bingham, 1988). Furthermore, the "Big-Fish-Little-Pond" effect (for overviews see Marsh, 2005) was vindicated for test anxiety by Zeidner & Schleyer (1999b), who reported that gifted students enrolled in a pullout program showed lower mean levels of test anxiety compared to gifted students in homogenous gifted classes.…”
Section: Anxiety: Trait State and Evaluativesupporting
confidence: 90%
“…Similarly, in the U.S., Reynolds and his coworkers (Reynolds & Bradley, 1983) and Davis and Connell (1985) reported lower anxiety in gifted compared to non-gifted elementary school students. Furthermore, the high academic self-efficacy of gifted students should serve to enhance their performance and concomitantly reduce their academic anxiety.…”
Section: Personalitymentioning
confidence: 83%
“…Indeed, if some adolescents experiencing academic difficulties seem to develop a very negative academic (perhaps even overall) self-esteem, and thus refuse to consider themselves "gifted" or "talented", others claim their intelligence and their belonging to the gifted adolescent category. This distinction between self-esteem and academic achievement concurs with the findings of Davis and Connell (1985) or Pajares (1996) when they suggested that gifted young people could base the evaluation of their intelligence more on the knowledge of their I.Q. score than on their actual academic achievements.…”
Section: Discussionsupporting
confidence: 77%
“…Research has suggested that perceived academic ability is related to depression. In a study of aptitude and achievement, underachievers exhibited lower perceived competence than peers of comparable abilities (Davis & Connell, 1985). Blechman, McEnroe, Carella, and Audette (1986) proposed that academically incompetent children may exhibit depressive symptoms.…”
mentioning
confidence: 99%